2007
DOI: 10.1007/s10534-007-9104-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron-induced oxidative stress in haemodialysis patients: a pilot study on the impact of diabetes

Abstract: In haemodialysis patients, higher lipid peroxidation is determined by higher body iron stores. The increase induced by iron infusion is accompanied by a loss in iron-binding antioxidant capacity and is more pronounced in diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…In the clinic, however, we were surprised by a small number of HHT patients who spontaneously volunteered that they could not use iron tablets or infusions to treat their iron deficiency because the iron treatments precipitated nosebleeds within hours. This prompted us to examine whether endothelial cells were modified by iron concentrations similar to those present in the bloodstream after iron tablets or infusions . Previous studies demonstrated toxicity at much higher iron concentrations, relevant to iron overload disorders or experimental endothelial models .…”
Section: Introductionmentioning
confidence: 99%
“…In the clinic, however, we were surprised by a small number of HHT patients who spontaneously volunteered that they could not use iron tablets or infusions to treat their iron deficiency because the iron treatments precipitated nosebleeds within hours. This prompted us to examine whether endothelial cells were modified by iron concentrations similar to those present in the bloodstream after iron tablets or infusions . Previous studies demonstrated toxicity at much higher iron concentrations, relevant to iron overload disorders or experimental endothelial models .…”
Section: Introductionmentioning
confidence: 99%
“…However, all IV iron products have the potential to have direct release of iron [non-transferrin bound iron (NTBI)] into plasma, a physicochemical characteristic that appears to be directly related to molecular weight, and drug clearance by the RES (Danielson 2004;Pai et al 2010;Balakrishnan et al 2009;Van Wyck et al 2004). Single and multi-dose studies of IV iron have demonstrated significant increases in biomarkers of oxidative stress in HD patients indicating that IV iron can induce lipid peroxidation, DNA damage and increase inflammatory mediators (Van Campenhout et al 2008;Kuo et al 2008;Garcia-Fernandez et al 2010). A comparative analysis of commercially available preparations has shown that in vitro that iron sucrose, sodium ferric gluconate and iron dextran induce oxidative stress but higher rates of cell death were apparent among iron sucrose, sodium ferric gluconate treated human proximal tubule cells (Zager et al 2002).…”
mentioning
confidence: 99%
“…Therefore, it is general recommendation not to use single IV bolus doses >100 mg. In vivo data on oversaturation have been published in humans after injection of 100 mg IS [12,23,44,45], and 62.5–125 mg iron-gluconate (IG) [25,46] and ID [47]. Once again, the interpretation of these data on oversaturation can be troublesome because of the possibility of direct assay interference with the IV iron agent.…”
Section: Discussionmentioning
confidence: 99%